L’émancipation par le savoir : à quelles conditions ? - François Galichet (Recherches en Éducation)
During a long time, emancipation was associated with knowledge. Education was supposed making freedom. Recently, this link between emancipation and knowledge is questioned. Within the critical sociology of Bourdieu, knowledge does not make free but causes selection and inequality. This separation puts back the importance of pedagogy in education. Knowledge is emancipating only if it is bound to definite educational conditions. Therefore, any pedagogy is also ethics and politics.